Seizures: Clinical Updates in Women's Health Care Primary and Preventive Care Review. Issue 1 (January 2021) - Hessler, Amy; Dolbec, Katelyn
Abstract : Abstract: Epilepsy is a common disease that affects 1.5 million women of childbearing age in the United States. Approximately 24, 000 women with epilepsy give birth each year. The challenges for women with epilepsy extend from menarche to postmenopause, including prepregnancy, pregnancy, intrapartum and postpartum periods, menopause, and postreproductive age. The most up-to-date neurology and epilepsy guidelines provided in this monograph will enable obstetrician–gynecologists to provide care to women with this complex condition across the life span.